Persimmon, loquat, fig, pomegranate and prickly pear in Israel - Blumenfeld A. (Underutilized fruit crops in the Mediterranean region, 1995)
Loquat culture in Israel occupies 300 ha in organized highly productive plantations. Almost all the cultivated varieties are local selections. Fig tree is well known but its culture was limited last years. Persimmon culture had a large development from the 70's to 1982. The major variety is 'Triumph'. Post-harvest technology is well developed.
First meeting of the CIHEAM Cooperative Working Group on Underutilized Fruit Crops in the Mediterranean Region, 1994/11/09-10, Zaragoza (Spain)